2011
DOI: 10.1111/j.1600-0838.2010.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring soccer skill performance: a review

Abstract: The ability to execute skilled movement patterns efficiently and effectively is the most important aspect of soccer performance and players must apply cognitive, perceptual and motor skills to rapidly changing situations. There have been attempts to measure these parameters for talent identification (or development) purposes and skill acquisition and intervention research; the aim of this review is to examine the strengths and limitations of these tests. High levels of perceptual and cognitive skill are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
212
0
28

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(270 citation statements)
references
References 44 publications
(90 reference statements)
6
212
0
28
Order By: Relevance
“…Tests of soccer-specific skill are usually more time-intensive and can offer lower repeatabilities than measures of athletic performance [23]. Furthermore, there are also disagreements over which skills are the most relevant [10]. Finally, many coaches still feel that assessment of skill is their domain, and not that of scientists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tests of soccer-specific skill are usually more time-intensive and can offer lower repeatabilities than measures of athletic performance [23]. Furthermore, there are also disagreements over which skills are the most relevant [10]. Finally, many coaches still feel that assessment of skill is their domain, and not that of scientists.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, variation in traits and performance among individuals drives success (as quantified in evolutionary biologists). Soccer is an ideal sport for an integrative study such as ours, because soccer enables one to identify, isolate and quantify the traits that potentially underlie the relative success of many individuals in multiple populations [10,34]. Soccer is the world's most popular team sport, played by more than 200 million registered competitors and transcends national, cultural, religious and gender boundaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ericsson [32] has argued that this type of method is particular relevant in sport where sequences of events are rarely if ever repeated in an exact form. Additionally, Ali [33] reported that using such instruments can enable scientists to carefully examine the core aspects of perceptual skill performance in soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Existen gran número de métodos científicos para evaluar el rendimiento físico (Ali, 2011). Sin embargo solo una minoría de los centros deportivos cuentan con laboratorios o equipo para evaluaciones sofisticadas.…”
Section: Introductionunclassified